Performance of GoFood MSEs Partnership: An Integration of Entrepreneurial Orientation, Marketing Capabilities, and Brand Orientation - Septi Kurnia Prastiwi; Asep Maulana Rohimat (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The current application of Gojek with its GoFood feature can serve the function as promotion media to consumers at the maximum extent for the Micro and Small Enterprises (MSEs) in the culinary business. Nevertheless, not all have been able to experience the improvement of this business performance in terms of the new application feature. Therefore, this study aims at investigating and analyzing the role of entrepreneurial orientation, marketing capability, and brand orientation to improve the performance of GoFood partnering SMEs. There were 112 samples of business partners in Surakarta participated in this study. The data analysis technique was by SEM using the application of AMOS 2.4. The research findings provide a conclusion that there is a significant effect of entrepreneurial orientation on marketing capabilities, brand orientation, and business performance. However, marketing capability and brand orientation were not proven to improve business performance; similarly, the mediation of entrepreneurial orientation through marketing capability and brand orientation was not supportive of business performance development. This study provides an actual contribution to the performance improvement of MSEs entrepreneurs through the digital application as an innovation and creativity of business players.